Identifying the geographical origin of Serra da Estrela PDO cheeses using fatty acids profiles - Lima, M.J. Reis (2020)
Serra da Estrela Cheese (SEC) is a Portuguese traditional cheese that bears a Protected Designation of Origin label, produced in a limited geographical region, using Raw ewe milk from "Churra Mondegueira" and "Bordaleira" autochthonus breeds; Wild thistle flower (Cynara cardunculusL.) and Salt